Therapeutic effects and safety of olcegepant and telcagepant for migraine: A meta-analysis - Yao, Gang; Yu, Tingmin; Han, Ximei; Mao, Xijing; Li, Bo (Neural regeneration research, 2013)
To evaluate the therapeutic effects and adverse reactions of olcegepant and telcagepant for the treatment of migraine. We identified studies using Medline (1966-01/2012-06), PubMed (1966-01/2012-06), Scopus (1980-01/2012-06), Cochrane Central Register of Controlled Trials (1980-01/2012-06) and China National Knowledge Infrastructure (1980-01/2012-06). The included studies were double-blind, randomized and placebo-controlled trials of olcegepant or telcagepant for the treatment of single acute migraine in patients with or without aura. Adverse reaction data were also included. Two independent investigators performed quality evaluation and data extraction using Jadad scoring. Meta-analyses were undertaken using RevMan 5.0.25 software. Pain relief rate, pain-free rate, and incidence of adverse reactions were measured in patients 2 and 24 hours after injection of olcegepant and oral telcagepant. Six randomized, controlled trials were included. Meta-analysis demonstrated that compared with placebo, the pain relief rate (odds ratio, OR = 5.21, 95% confidence interval, CI: 1.91-14.2, P < 0.01) and pain-free rate (OR = 31.11, 95% CI: 3.80-254.98, P < 0.01) significantly increased 2 hours after 2.5 mg/d olcegepant treatment. Pain relief rate and pain-free rate 2 and 24 hours after treatment with telcagepant 150 mg/d and 300 mg/d were superior to placebo (P < 0.01). Moreover, the remission rate of unrelenting headache was higher after 24 hours of 300 mg/d telcagepant treatment compared with 150 mg/d (OR = 0.78, 95% CI: 0.62-0.97, P < 0.05). The incidence of adverse reactions with olcegepant was not significantly greater than placebo (P = 0.28), but within 48 hours of administration of telcagepant 300 mg/d, the incidence of adverse reactions was higher than placebo (OR = 1.21, 95% CI: 1.04-1.42, P < 0.01). Few studies have compared the therapeutic effects of olcegepant and telcagepant. The calcitonin-gene-related peptide receptor antagonists olcegepant and telcagepant have shown good therapeutic effects in the treatment of migraine. Moreover, the incidence of adverse reactions compares favorably with placebo, although liver transaminases may become elevated after long-term use.